The family-school relationship in primary education: Parents’ perspectives in the age of “the minimal self” - Dusi, Paola (International Journal about Parents in Education, 2023)
As many scholars in different disciplines have highlighted (Lasch, 1979; Lipovetsky, 1983; Giroux, 2004; Pulcini, 2009; Mayo, 2014;), Western societies are experiencing a phase of socioanthropological upheaval driven by the social and economic effects of neoliberalism. The question arises: are these changes affecting the relationship between schools and students’ families? And if so, in what way? This article begins with a brief summary of what we mean when we talk of “socioanthropological change” in this context, before going on to explore the perspectives – in regard to the school-family relationship – of what is an increasingly heterogeneous group, namely the parents of children in primary education. How do the parents of today experience this relationship? What expectations and beliefs inform their conception of it? The (still-ongoing) study described in this article was initiated in large part to address questions such as these. A key phase of the research carried out so far comprised the administration of semi-structured interviews with Italian parents of primary school children. The results discussed here are based on 101 interviews administered in 2017 and 2018 with a total of 103 parents from various towns/provinces in northern Italy (Lombardy, Veneto, Trentino-Alto Adige). The participants (all volunteers) were selected using a snowball sampling method. The study was intended, ultimately, as an examination of experience (Polkinghorne, 1989) in that it sought to achieve a faithful representation of what the participants expressed. We decided this was best served by a naturalistic paradigm and a phenomenological-eidetic approach whereby, in order to apprehend the true qualities of things, the researcher’s personal theories are set aside. The analysed data paints a mixed picture, with a range of different parent “types” who, in one sense or another, are looking for support to allow them to better fulfil their role as a parent.